Systematic Review and Meta-Analysis of Acute Mortality and Complication Rates Following Leadless Pacemaker Placement Using National-Level Data - Akmoldir Sarsenbayeva; Adil Baimbetov; Aras Puodziukynas; Bolatbek Baimakhanov; Alexander Sapunov; Kenzhebek Bizhanov (Medicina)
Background and Objectives: Leadless pacemakers provide an innovative alternative to traditional transvenous pacemakers for managing cardiac arrhythmias. The objective of this systematic review is to conduct a meta-analysis comparing acute complication and mortality rates associated with leadless pacemakers versus transvenous pacemaker placements using national-level data. Specifically, we aim to summarize the current evidence and calculate pooled odds ratios for acute overall complications, acute device-related complications, and acute mortality to assess the early safety outcomes of leadless pacemaker placement relative to traditional transvenous pacemakers. Materials and Methods: A systematic search of PubMed, Scopus, ScienceDirect, and Google Scholar was conducted by two independent researchers using a predefined search protocol. The search included articles published up to 10 October 2024, without limits on review depth. Studies were included if they provided national-level data comparing leadless pacemaker and traditional pacemaker recipients in terms of acute mortality, acute overall complications, and acute device-related complications. Outcomes were pooled to calculate odds ratios using a random-effects model in RStudio (version 2024.12.1+563). Results: A total of five studies met the eligibility criteria. The pooled odds ratio for acute mortality was 2.03 (95% CI: 0.65–6.34, I2 = 99%; p < 0.01), for acute overall complications was 1.08 (95% CI: 0.45–2.61, I2 = 99%; p < 0.01), and for acute device-related complications was 1.02 (95% CI: 0.23–4.44, I2 = 99%; p < 0.01). Conclusions: The reviewed studies suggest that leadless pacemakers offer a promising alternative to transvenous pacemakers, offering a comparable short-term safety profile. Ongoing technological advancements may further enhance their applicability in clinical practice.